Suicide Among Diverse Youth A Case-Based Guidebook (Springer International Publishing, 2018)
This book provides a comprehensive review of the complex, growing mental health challenges faced by culturally diverse populations of children and adolescents.Suicide Among Diverse Youth: A Case-Based Guidebook is the first book of its kind, and is designed specifically to bridge the knowledge and skills gap encountered by most clinicians dealing with youth from diverse cultural backgrounds, particularly those different than that of the clinician. The title begins with two introductory chapters, which cover cultural aspects of suicidality among youth, culturally informed treatment of suicidality with diverse youth, and exampl es of preventative approaches. These are followed by population specific chapters which cover a broad spectrum of diverse populations, including underserved ethnic and racial populations in the United States, LGBTQ youth, as well as various immigrant populations from Eastern European and Middle Eastern countries. These case-based chapters are structured in a cohesive, easy-to-read format that promotes ease of reference, beginning with a clinical case report, review of literature, unique characteristics and risk factors associated with suicidality, and evidence-based practice provided by the authors from their considerable experience. The authors are often from the same ethnic, racial, or cultural group that they discuss in their writings; providing experiential knowledge where scientific knowledge is lacking. Suicide Among Diverse Youth: A Case-Based Guidebook is a unique resource that offers the clinical material needed to treat diverse adolescent patients with sensitive, intersectional, and culturally-informed care, and will provide an indispensable resource for medical professionals working with, and caring for these patients.